Whole brain radiation therapy verification using 2D gamma analysis method - Zainodin, Nik Nurul Afina Wan (2020)
Whole-brain radiation therapy (WBRT) is a standard radiotherapy treatment for the patients with multiple brain metastases. The efficiency of the dose calculation algorithm and the accuracy of the dose delivered to the patient is crucial in radiotherapy. In this study, Pencil Beam (PB) and Collapsed Cone (CC) algorithms in Oncentra Masterplan treatment planning system (TPS) were compared to assess their impact on the three-dimensional (3D) planning of the WBRT. Besides, this study aim is to establish a procedure of pre-treatment patient-specific quality assurance using EBT3 film in the heterogeneous anthropomorphic head phantom. A 3D conformal radiotherapy (CRT) of WBRT plans were constructed using both algorithms. The doses in the planning target volume (PTV), organs at risk (OAR) and monitor unit (MU) calculated by the algorithms were compared. Furthermore, the accuracy of both algorithms was evaluated using EBT3 film by comparing the gamma index passing rate in a Verisoft software. The comparison between the PB and CC algorithms in the TPS calculation showed that the dose distribution using the PB algorithm gave a higher maximum and mean dose to the PTV compared to the CC algorithm by 0.15% and 0.1%. However, the MU calculated by using the PB algorithm was 420.26 MU and it is lower than the CC algorithm by 0.99%. The p-value for this study was >0.05, which indicates that there is no significant difference between these two algorithms for the gamma index analysis. The CC algorithm showed a better accuracy than the PB algorithm since the measured dose in the film was closer to the calculated dose in the TPS with a higher gamma index passing rate than the PB algorithm. The CC algorithm gave the passing rate of 87.25% using 3 mm/3% (DTA/DD) method than PB algorithm with 79.95%. The 2D gamma index analysis using EBT3 film is suggested to practice as the pre-treatment patient specific quality assurance (QA) for the 3D-CRT WBRT plan.